Online presentations for instruction: an overview - Ruth, Fabian; Lipphardt, Carmen; Schickel, Marco; Ruth-Herbein, Evelin; Ringeisen, Tobias (Frontiers in Education, 2025)
Online presentations have become a cost-efficient and contemporary format for knowledge transfer. The associated competence is in demand at all levels of education and in many work contexts as presenting online contributes to educational and professional success. Despite its growing importance, it lacks a research-based overview regarding the definition, performance antecedents and recommendations how to foster online presentation competence. Based on an literature overview, a framework was developed to conceptualize online presentations and their underlying competence facets for instruction. According to this, presentation behavior and presentation performance in online settings is influenced by an interplay of the key factors consisting of (1) speaker’s competence-constituting characteristics, (2) efforts to prepare and practice the presentation, (3) within-speaker processes, and (4) features of the setting. Future empirical studies should examine structure and validity of this framework in more detail. The educational focus on online presentations can be concluded that by deriving a research-based training approach that fit all levels of education and professional training. That intervention model can also serve as a starting point for more research on presentation training programs to promote online presentation competence to disseminate its application to diverse professional contexts such as business or healthcare.